Laccase composite material, preparation method and application thereof, and phenol-containing wastewater treatment method

By immobilizing laccase on a foam carbon support, a laccase composite material was prepared, which solved the stability and reusability of laccase in wastewater treatment, and achieved efficient degradation of phenolic compounds and easy separation and recovery of materials.

CN119707128AActive Publication Date: 2025-03-28INNOVATION CENTER OF YANGTZE RIVER DELTA ZHEJIANG UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411972182.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art has problems such as poor stability, ease of inactivation, difficulty in recycling and reuse when treating phenolic compounds, which limits the widespread application of laccase in wastewater treatment.

Method used

A laccase composite material was prepared by immobilizing laccase on a foamed carbon support. The substrate of this material is foam carbon, with a specific surface area of ​​150 to 200 m2/g, and a minimum size greater than or equal to 0.2 cm, and a loading of laccase is 1 to 10 wt%.

Benefits of technology

It realizes easy separation and recovery of laccase composite materials and water bodies, while improving the degradation efficiency of phenolic compounds, solving the problems of stability and reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707128A_ABST
    Figure CN119707128A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wastewater treatment, and provides a laccase composite material, a preparation method and application thereof, and a phenolic wastewater treatment method. The laccase composite material provided by the invention comprises a matrix and laccase attached to the matrix, the matrix is foamy carbon, and the specific surface area of the foamy carbon is 150-200m < 2 > / g; the minimum size of the foamy carbon is greater than or equal to 0.2 cm; the loading capacity of the laccase is 1 to 10 weight percent. The minimum size of the matrix foamy carbon is controlled to be greater than or equal to 0.2 cm, so that the laccase composite material is easily separated from a water body and is easy to recycle; meanwhile, the specific surface area of the foamy carbon is controlled to be 150-200m < 2 > / g, and the loading capacity of the laccase is 1-10wt%, so that the high degradation efficiency of the laccase composite material on the phenolic compounds is also ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, in particular to a laccase composite material and a preparation method and application thereof, and a method for treating phenol-containing wastewater. Background Art

[0002] The presence of phenolic compounds poses a serious threat to the ecological environment and human health. Phenolic compounds are highly toxic and stable. Even a small amount of them entering the environment will cause a high public health risk, and it is difficult to remove them from the environment through self-purification. Traditional physical and chemical methods, such as adsorption and chemical oxidation, are effective in some cases, but are often accompanied by high energy consumption, high costs and possible secondary pollution. Therefore, it is particularly important to find an efficient, green and environmentally friendly treatment method.

[0003] Laccase is a copper-containing polyphenol oxidase that is widely present in a variety of organisms. It is considered to be an ideal biocatalyst for treating phenolic compounds because of its wide substrate spectrum and efficient catalytic ability. However, in practical applications, free laccase faces problems such as poor stability, easy inactivation, and difficulty in recovery and reuse. These problems limit the widespread application of laccase in wastewater treatment. In order to solve these problems, immobilization technology was introduced, aiming to improve the stability and reusability of laccase and enhance its catalytic efficiency by fixing it on a certain carrier.

[0004] In the prior art, laccase is fixed on a carrier, and the obtained laccase composite material is not easy to be separated from the water body. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a laccase composite material and its preparation method and application, and a method for treating phenol-containing wastewater. The laccase composite material provided by the present invention is easy to separate from water and has high efficiency in degrading phenolic compounds.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a laccase composite material, comprising a substrate and a laccase attached to the substrate;

[0008] The substrate is foamed carbon, and the specific surface area of ​​the foamed carbon is 150 to 200 m 2 / g;

[0009] The minimum size of the foamed carbon is greater than or equal to 0.2 cm;

[0010] The loading amount of the laccase is 1-10 wt %.

[0011] Preferably, the method for preparing the foamed carbon comprises the following steps:

[0012] The lignin and the inorganic alkali solution are mixed and subjected to hydrothermal treatment to obtain a hydrothermal system;

[0013] The hydrothermal system is subjected to acid precipitation to obtain a carbon precursor;

[0014] The carbon precursor is heat treated to obtain the foamed carbon.

[0015] Preferably, the inorganic alkali in the inorganic alkali solution includes sodium hydroxide and / or potassium hydroxide, the concentration of the inorganic alkali solution is 0.8-1.2 mol / L, and the dosage ratio of the lignin to the inorganic alkali solution is 1 g:40-50 mL;

[0016] The temperature of the hydrothermal treatment is 160-200° C., and the time is 5-12 hours.

[0017] Preferably, the acid precipitation reagent is hydrochloric acid, and the concentration of hydrochloric acid in the acid precipitation system is 0.4-0.6 mol / L.

[0018] Preferably, the heat treatment comprises sequentially performing a first heat treatment and a second heat treatment;

[0019] The temperature of the first heat treatment is 600-700°C, the holding time is 1-3h, and the heating rate to the temperature of the first heat treatment is 5-15°C / min;

[0020] After the first heat treatment, directly raising the temperature to perform a second heat treatment;

[0021] The temperature of the second heat treatment is 750-800° C., the holding time is 2-4 hours, and the heating rate to the temperature of the second heat treatment is 5-15° C. / min.

[0022] The present invention also provides a method for preparing the laccase composite material described in the above technical solution, comprising the following steps:

[0023] The foamed carbon is impregnated in the laccase solution and then immobilized to obtain the laccase composite material.

[0024] Preferably, the concentration of the laccase solution is 0.5 to 1.5 g / L;

[0025] After the foam carbon is immersed in the laccase solution, the concentration of the foam carbon in the obtained system is 1-2 g / L.

[0026] Preferably, the immobilization time is 0.5 to 3 hours, and the immobilization is performed under shaking conditions, and the shaking rate is 100 to 200 rpm.

[0027] The present invention also provides the use of the laccase composite material described in the above technical solution or the laccase composite material prepared by the preparation method described in the above technical solution in degrading phenolic compounds.

[0028] The present invention also provides a method for treating phenol-containing wastewater, comprising the following steps:

[0029] placing the laccase composite material described in the above technical solution or the laccase composite material prepared by the preparation method described in the above technical solution in wastewater containing phenolic compounds for treatment;

[0030] The concentration of phenolic compounds in the phenolic compound-containing wastewater is 50 to 100 mg / L;

[0031] The concentration of the laccase composite material in wastewater containing phenolic compounds is greater than or equal to 0.2 mg / mL.

[0032] The invention provides a laccase composite material.

[0033] The present invention controls the minimum size of the matrix foam carbon to be greater than or equal to 0.2 cm, so that the laccase composite material is easily separated from the water body and easy to recover; at the same time, the specific surface area of ​​the foam carbon is controlled to be 150-200 m 2 / g, and the loading amount of laccase is 1-10wt%, which also ensures the high degradation efficiency of laccase composite materials on phenolic compounds.

[0034] The present invention also provides a method for preparing the laccase composite material described in the above technical solution. The preparation method provided by the present invention is simple to operate.

[0035] Furthermore, the present invention limits the concentration of the laccase solution to 0.5-1.5 g / L; after the foamed carbon is immersed in the laccase solution, the concentration of the foamed carbon in the obtained system is 1-2 g / L, so that the laccase can be more evenly loaded on the foamed carbon, thereby improving the degradation efficiency of the laccase composite material on phenolic compounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope photo of the lignin-based foamed carbon obtained in Example 1;

[0037] Figure 2 This is a physical photo of the lignin-based foam carbon obtained in Example 1. DETAILED DESCRIPTION

[0038] The present invention provides a laccase composite material, comprising a substrate and a laccase attached to the substrate;

[0039] The substrate is foamed carbon, and the specific surface area of ​​the foamed carbon is 150 to 200 m 2 / g;

[0040] The minimum size of the foamed carbon is greater than or equal to 0.2 cm;

[0041] The loading amount of the laccase is 1-10 wt %.

[0042] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0043] The laccase composite material provided by the present invention comprises a matrix, wherein the matrix is ​​foamed carbon, and the specific surface area of ​​the foamed carbon is 150 to 200 m 2 / g, preferably 150m 2 / g, 155m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g or 200m 2 In the present invention, the minimum size of the foamed carbon is greater than or equal to 0.2 cm, and further, the minimum size of the foamed carbon is preferably 0.2 to 10 cm.

[0044] In the present invention, the method for preparing the foamed carbon preferably comprises the following steps:

[0045] The lignin and the inorganic alkali solution are mixed and subjected to hydrothermal treatment to obtain a hydrothermal system;

[0046] The hydrothermal system is subjected to acid precipitation to obtain a carbon precursor;

[0047] The carbon precursor is heat treated to obtain the foamed carbon.

[0048] The present invention mixes lignin and an inorganic alkali solution, performs a hydrothermal treatment, and obtains a hydrothermal system. In the present invention, the inorganic alkali in the inorganic alkali solution preferably includes sodium hydroxide and / or potassium hydroxide, and is more preferably sodium hydroxide. In the present invention, the concentration of the inorganic alkali solution is preferably 0.8 to 1.2 mol / L, and is particularly preferably 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L or 1.2 mol / L. In the present invention, the amount ratio of the lignin and the inorganic alkali solution is preferably 1 g: 40 to 50 mL, and is particularly preferably 1 g: 40 mL, 1 g: 45 mL or 1 g: 50 mL.

[0049] In the present invention, the mixing of the lignin and the inorganic alkali solution is preferably carried out under stirring, and the stirring speed is preferably 100-150rpm, specifically preferably 100rpm, 110rpm, 120rpm, 130rpm, 140rpm or 150rpm; the temperature is preferably 20-30°C, specifically preferably 20°C, 25°C or 30°C; the time is preferably 20-40min, specifically preferably 20min, 30min or 40min.

[0050] In the present invention, the temperature of the hydrothermal treatment is preferably 160-200°C, specifically preferably 160°C, 170°C, 180°C, 190°C or 200°C; the time is preferably 5-12h, specifically preferably 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h. In the present invention, the hydrothermal treatment can dissolve the lignin and remove the insoluble impurities in the lignin, thereby purifying the lignin.

[0051] In the present invention, the hydrothermal treatment is preferably carried out in a polytetrafluoroethylene digestion tank.

[0052] After the hydrothermal treatment, the present invention preferably further comprises: cooling the obtained hydrothermal treatment liquid to room temperature to obtain the hydrothermal system.

[0053] After obtaining the hydrothermal system, the present invention performs acid precipitation on the hydrothermal system to obtain a carbon precursor.

[0054] In the present invention, the acid precipitation reagent is preferably hydrochloric acid, and the concentration of hydrochloric acid in the acid precipitation system is preferably 0.4-0.6 mol / L, specifically preferably 0.4 mol / L, 0.5 mol / L or 0.6 mol / L.

[0055] In the present invention, the temperature of the acid precipitation is preferably 20-30°C, specifically preferably 20°C, 25°C or 30°C; the time is preferably 20-40min, specifically preferably 20min, 30min or 40min. In the present invention, the acid precipitation is preferably carried out under stirring conditions, and the stirring speed is preferably 100-150rpm, specifically preferably 100rpm, 110rpm, 120rpm, 130rpm, 140rpm or 150rpm. In the present invention, the acid precipitation can precipitate the dissolved lignin.

[0056] After the acid precipitation, the present invention preferably further comprises: centrifuging the obtained acid precipitation liquid to collect solids; washing and drying the solids in sequence to obtain the carbon precursor. In the present invention, the centrifugal speed is preferably 2000-40000rpm, specifically preferably 2000rpm, 3000rpm or 4000rpm. In the present invention, the washing reagent is preferably water, more preferably deionized water; the number of washings is preferably 3 times, and the washing can remove acids and salts. In the present invention, the drying temperature is preferably 80°C, and the drying time is preferably 12h.

[0057] After obtaining the carbon precursor, the present invention performs heat treatment on the carbon precursor to obtain the foamed carbon.

[0058] In the present invention, the heat treatment preferably includes performing a first heat treatment and a second heat treatment in sequence.

[0059] In the present invention, the temperature of the first heat treatment is preferably 600-700°C, and is preferably 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C; the holding time is preferably 1-3h, and is preferably 1h, 2h or 3h; the heating rate to the temperature of the first heat treatment is preferably 5-15°C / min, and is preferably 5°C / min, 10°C / min or 15°C / min. In the present invention, the first heat treatment is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably nitrogen. In the present invention, the first heat treatment is preferably carried out in a tubular furnace.

[0060] After the first heat treatment, the present invention preferably directly raises the temperature to perform a second heat treatment.

[0061] In the present invention, the temperature of the second heat treatment is preferably 750-800°C, specifically preferably 750°C, 760°C, 770°C, 780°C, 790°C or 800°C; the holding time is preferably 2-4h, specifically preferably 2h, 3h or 4h; the heating rate to the temperature of the second heat treatment is preferably 5-15°C / min, specifically preferably 5°C / min, 10°C / min or 15°C / min. In the present invention, the second heat treatment is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably nitrogen. In the present invention, the second heat treatment is preferably carried out in a tubular furnace.

[0062] After the heat treatment, the temperature is preferably lowered to room temperature to obtain the foamed carbon.

[0063] The laccase composite material provided by the present invention comprises a laccase attached to the substrate. In the present invention, the loading amount of the laccase is 1 to 10 wt%, and is preferably 1 wt%, 2 wt%, 3 wt%, 4 wt%, 4.2 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 8.1 wt%, 9 wt%, 9.8 wt% or 10 wt%.

[0064] In a specific embodiment of the present invention, the laccase gene of the laccase is preferably AA1_Bin30_Lac. In the present invention, the laccase gene is preferably screened from a metagenome (BioProject ID: PRJNA785376) to obtain a laccase gene with strong structural stability. In the present invention, the method for obtaining the laccase gene preferably includes gene synthesis, heterologous expression and separation and purification to obtain recombinant laccase. In a specific embodiment of the present invention, the laccase gene is preferably obtained according to the patent with publication number CN114574453A.

[0065] The present invention also provides a method for preparing the laccase composite material described in the above technical solution, comprising the following steps:

[0066] The foamed carbon is impregnated in the laccase solution and then immobilized to obtain the laccase composite material.

[0067] In the present invention, the concentration of the laccase solution is preferably 0.5-1.5 g / L, specifically preferably 0.5 g / L, 1 g / L or 1.5 g / L.

[0068] In the present invention, after the foamed carbon is immersed in the laccase solution, the concentration of the foamed carbon in the obtained system is preferably 1-2 g / L, specifically preferably 1 g / L, 1.5 g / L or 2 g / L.

[0069] In the present invention, the immobilization time is preferably 0.5 to 3 hours, specifically preferably 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours; the immobilization is preferably carried out under oscillation conditions, and the oscillation rate is preferably 100 to 200 rpm, specifically preferably 100 rpm, 150 rpm or 200 rpm.

[0070] After the immobilization, the present invention preferably further comprises: washing, separating and vacuum drying the obtained immobilized liquid in sequence to obtain the laccase composite material.

[0071] The present invention also provides the use of the laccase composite material described in the above technical solution or the laccase composite material prepared by the preparation method described in the above technical solution in degrading phenolic compounds.

[0072] The present invention also provides a method for treating phenol-containing wastewater, comprising the following steps:

[0073] The laccase composite material described in the above technical solution or the laccase composite material prepared by the preparation method described in the above technical solution is placed in wastewater containing phenolic compounds for treatment.

[0074] In the present invention, the phenolic compound preferably includes, but is not limited to, one or more of hydroquinone, phenol, cresol, 2,4-dichlorophenol, 2,4,6-trichlorophenol and p-nitrophenol.

[0075] In the present invention, the concentration of phenolic compounds in the phenolic compound-containing wastewater is preferably 50-100 mg / L, specifically preferably 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L or 100 mg / L.

[0076] In the present invention, the pH value of the wastewater containing phenolic compounds is preferably 4.5 to 5.5, and specifically preferably 4.5, 5 or 5.5.

[0077] In the present invention, the concentration of the laccase composite material in the wastewater containing phenolic compounds is greater than or equal to 0.2 mg / mL, and is preferably 0.2-10 mg / mL.

[0078] In the present invention, the treatment is preferably carried out under oscillation conditions, and the rotation speed of the oscillation is preferably 100 to 200 rpm, and specifically preferably 100 rpm, 150 rpm or 200 rpm.

[0079] After the treatment, the present invention preferably further comprises: separating the obtained treated liquid and collecting the laccase composite material.

[0080] In the present invention, the separation method is preferably filtration.

[0081] In the present invention, the laccase composite material is separated from the water body, which can reduce the secondary pollution of the laccase composite material to the water body.

[0082] The laccase composite material provided by the present invention, its preparation method and application, and the method for treating phenol-containing wastewater are described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.

[0083] Example 1

[0084] Preparation method of lignin-based foamed carbon:

[0085] (1) Dissolve 1g of lignin in 50mL of 1mol / L NaOH solution, stir at 25℃ for 30min, transfer to a polytetrafluoroethylene digestion tank, perform hydrothermal treatment at 180℃ for 6h, then take out the polytetrafluoroethylene digestion tank and cool to room temperature to obtain a black mixture, which is the hydrothermal system; transfer the black mixture to a 500mL wide-mouth bottle for acid precipitation, and continuously drip 50mL of 2mol / L hydrochloric acid into the black mixture to make the concentration of hydrochloric acid in the system 0.5mol / L, stir at 25℃ and 100rpm for 30min, after brown precipitate appears, centrifuge at 3000rpm to collect solid. Wash the brown precipitate three times with deionized water to remove hydrochloric acid and NaCl, and then dry at 80℃ for 12h to obtain a carbon precursor.

[0086] (2) Take 2.0 g of the above carbon precursor and place it in a tube furnace. 2 Under the atmosphere, the temperature was increased to 600°C at a heating rate of 10°C / min and kept for 2h; the temperature was further increased to 800°C at a heating rate of 10°C / min and kept for 3h, and then cooled to room temperature to obtain lignin-based foamed carbon.

[0087] The microscopic morphology of the obtained lignin-based foam carbon was observed using a scanning electron microscope. Figure 1 As shown, from Figure 1 It can be seen that there are connecting channels between the holes, forming a connected pore network. The shapes of the pores are circular, elliptical, etc. The surface is rough and cracked, and the pores are evenly distributed on the surface of the material, forming a relatively regular structure.

[0088] Figure 2 This is a physical photo of the obtained lignin-based foam carbon.

[0089] The specific surface area and pore size of the lignin-based foamed carbon were determined by the BET method. The results showed that the specific surface area of ​​the obtained lignin-based foamed carbon was 155.5504 m 2 / g, and the average pore size is 3.3μm.

[0090] Example 2

[0091] Preparation of laccase:

[0092] Acquisition of laccase gene: A laccase gene (AA1_Bin30_Lac) with strong structural stability was screened out from the metagenome (BioProjectID: PRJNA785376). Recombinant laccase was obtained by gene synthesis, heterologous expression and separation and purification according to the patent publication number CN114574453A. The concentration was detected by SDS-PAGE, and the result was: 1.0 mg / mL.

[0093] Laccase activity and stability test: The standard substrate ABTS was selected to determine the activity of laccase. The specific process was: set up a 700 μL reaction system, containing 600 μL Tris-HCl solution, 50 μL ABTS, 50 μL enzyme solution with a concentration of 1.0 mg / mL, and adjust the pH value of the reaction system to 5.0; react at 20°C, 25°C, and 30°C for 5 minutes, measure the change in absorbance at 420 nm, and define the amount of enzyme required to oxidize 1 μmol / LABTS per minute as one laccase activity unit.

[0094] A 700 μL reaction system was set up, containing 600 μL Tris-HCl solution, 50 μL ABTS, and 50 μL 1.0 mg / mL enzyme solution, and the pH value of the reaction system was adjusted to 4.5, 5.0, 5.5 and 6.0; the reaction was carried out at 25°C for 5 min, and the change in absorbance was measured at 420 nm. The amount of enzyme required to oxidize 1 μmol / LABTS per minute was defined as one laccase activity unit.

[0095] The results are shown in Table 1.

[0096] Table 1 Laccase activity test results

[0097]

[0098] It can be seen from Table 1 that the enzyme activity is optimal when the temperature is between 25 and 30°C and the pH value is around 5.0.

[0099] Example 3

[0100] The lignin-based foam carbon obtained in Example 1 was cut into a size of 1.0 cm × 1.0 cm × 0.2 cm, and added to a laccase solution with an initial laccase concentration of 0.5 g / L at concentrations of 1.0 g / L, 1.5 g / L, and 2.0 g / L, and shaken in a shaker (150 rpm) for 2 h to complete the immobilization of the laccase. After washing, separation, and vacuum drying, a laccase composite material was obtained.

[0101] The BCA method was used to test the concentration of laccase in the laccase solution before and after the reaction, and the amount of enzyme adsorbed per unit carrier of each laccase composite material under different lignin-based foam carbon concentrations was calculated. The result showed that when the concentration of lignin-based foam carbon was 2.0 g / L, the loading amount of laccase was as high as 4.2 wt%.

[0102] The lignin-based foam carbon obtained in Example 1 was cut into a size of 1.0 cm × 1.0 cm × 0.2 cm, and added at a concentration of 2.0 g / L into laccase solutions with initial laccase concentrations of 0.5 g / L, 1.0 g / L, and 1.5 g / L, respectively. The mixture was shaken in a shaker (150 rpm) for 2 h to complete the immobilization of the laccase. After washing, separation, and vacuum drying, a laccase composite material was obtained.

[0103] The concentration of laccase in the laccase solution before and after the reaction was tested by the BCA method, and the amount of enzyme adsorbed per unit carrier of each laccase composite material was calculated at different initial laccase concentrations. The results showed that the laccase solution with an initial laccase concentration of 1.5 g / L had a high laccase loading of 8.1 wt%.

[0104] The lignin-based foam carbon obtained in Example 1 was cut into a size of 1.0 cm × 1.0 cm × 0.2 cm, and added to a laccase solution with an initial laccase concentration of 1.5 g / L at a concentration of 2.0 g / L. The mixture was shaken in a shaker (150 rpm) for 0.5 h, 1 h, 1.5 h, 2.0 h, and 3.0 h, respectively, to complete the immobilization of the laccase. After washing, separation, and vacuum drying, a laccase composite material was obtained.

[0105] The concentration of the enzyme before and after the reaction was tested by the BCA method, and the amount of enzyme adsorbed per unit carrier of each laccase composite material obtained at different immobilization times was calculated. The result showed that when the immobilization time was 2 h, the loading amount of laccase was as high as 9.8 wt%.

[0106] Example 4

[0107] The lignin-based foamed carbon obtained in Example 1 was cut into a size of 1.0 cm×1.0 cm×0.2 cm, and added to a laccase solution with an initial laccase concentration of 1.5 g / L at a concentration of 2.0 g / L. The mixture was shaken in a shaker (150 rpm) for 2 h to complete the immobilization of the laccase. After washing, separation, and vacuum drying, a laccase composite material was obtained, wherein the laccase loading was 9.8 wt%.

[0108] Application Example 1

[0109] The phenolic compound hydroquinone was added into deionized water to form simulated phenol-containing wastewater with a phenolic compound concentration of 100 mg / L, and the pH value of the simulated phenol-containing wastewater was adjusted to 5.0.

[0110] The laccase composite material obtained in Example 4 was added to the simulated phenolic wastewater at 0.3 mg / mL and shaken at 150 rpm for 10 h. The concentration of phenolic compounds in the obtained simulated phenolic wastewater was 0.39 mg / L, which was lower than the national sewage discharge standard (CJ343-2010) of 0.5-1.0 mg / L.

[0111] After the reaction is completed, the laccase composite material is directly removed from the simulated phenol-containing wastewater through physical separation and recycled for reuse.

[0112] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A laccase composite material, characterized in that: comprising a substrate and a laccase attached to the substrate; The substrate is foamed carbon, and the specific surface area of ​​the foamed carbon is 150 to 200 m 2 / g; The minimum size of the foamed carbon is greater than or equal to 0.2 cm; The loading amount of the laccase is 1-10 wt %.

2. The laccase composite material according to claim 1, characterized in that: The preparation method of the foamed carbon comprises the following steps: The lignin and the inorganic alkali solution are mixed and subjected to hydrothermal treatment to obtain a hydrothermal system; The hydrothermal system is subjected to acid precipitation to obtain a carbon precursor; The carbon precursor is heat treated to obtain the foamed carbon.

3. The laccase composite material according to claim 2, characterized in that: The inorganic alkali in the inorganic alkali solution includes sodium hydroxide and / or potassium hydroxide, the concentration of the inorganic alkali solution is 0.8-1.2 mol / L, and the dosage ratio of the lignin to the inorganic alkali solution is 1 g:40-50 mL; The temperature of the hydrothermal treatment is 160-200° C., and the time is 5-12 hours.

4. The laccase composite material according to claim 2, characterized in that: The acid precipitation reagent is hydrochloric acid, and the concentration of hydrochloric acid in the acid precipitation system is 0.4-0.6 mol / L.

5. The laccase composite material according to claim 2, characterized in that: The heat treatment includes sequentially performing a first heat treatment and a second heat treatment; The temperature of the first heat treatment is 600-700°C, the holding time is 1-3h, and the heating rate to the temperature of the first heat treatment is 5-15°C / min; After the first heat treatment, directly raising the temperature to perform a second heat treatment; The temperature of the second heat treatment is 750-800° C., the holding time is 2-4 hours, and the heating rate to the temperature of the second heat treatment is 5-15° C. / min.

6. The method for preparing the laccase composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The foamed carbon is impregnated in the laccase solution and then immobilized to obtain the laccase composite material.

7. The preparation method according to claim 6, characterized in that: The concentration of the laccase solution is 0.5 to 1.5 g / L; After the foam carbon is immersed in the laccase solution, the concentration of the foam carbon in the obtained system is 1-2 g / L.

8. The preparation method according to claim 6 or 7, characterized in that: The immobilization time is 0.5 to 3 hours, and the immobilization is carried out under shaking conditions, and the shaking rate is 100 to 200 rpm.

9. Use of the laccase composite material according to any one of claims 1 to 5 or the laccase composite material prepared by the preparation method according to any one of claims 6 to 8 in degrading phenolic compounds.

10. A method for treating phenol-containing wastewater, characterized in that: The following steps are involved: placing the laccase composite material according to any one of claims 1 to 5 or the laccase composite material prepared by the preparation method according to any one of claims 6 to 8 into wastewater containing phenolic compounds for treatment; The concentration of phenolic compounds in the phenolic compound-containing wastewater is 50 to 100 mg / L; The concentration of the laccase composite material in wastewater containing phenolic compounds is greater than or equal to 0.2 mg / mL.

Citation Information

Patent Citations

  • Method for removing phenol pollutants in water body by using immobilized laccase based on magnetic mesoporous carbon

    CN102329008A

  • Hollow mesoporous carbon immobilized laccase and preparation method

    CN107893066A

  • Preparation and application of biomass-based porous carbon material based on platanus orientalis seeds

    CN109626370A

  • Wood biomass-based porous carbon material prepared by high-temperature hydrothermal assisted cellulase hydrolysis, and application and method thereof

    CN113247893A